Media memorial discourses and memory struggles in Slovenia: Transforming memories of the Second World War and Yugoslavia. (August 2019) - Pušnik, Maruša
The radical break between two national contexts in 1991, when Slovenia seceded from Yugoslavia, and Slovenia's integration into the European Union in 2004, has brought changes to the collective memory of the Slovenian nation. In this article, I investigate how Delo, a major Slovenian daily newspaper, has been involved in memory struggles to present new memorial discourses that are in accordance with the new national politics. A large part of the common Yugoslav past has been reinvented for the present political and ideological purposes of European integration, whereby the Second World War and the Partisan movement, which once signified a common Yugoslav life, have become a contested issue. The focus of the critical narrative analysis is put on those general narrative templates that underlie specific news narratives about the Second World War and socialist Yugoslavia. Over the last 25 years, dominant media have strengthened memory struggles in the Slovenian public realm and have created revisionist narratives of the Second World War and the post-war past.